Successful treatment of phlegmasia cerulea dolens with percutaneous thrombectomy and catheter-directed thrombolysis: A case report. Issue 47 (25th November 2022) - Chang, Ching-Tang; Chang, Ching-Di
Abstract : Introduction: Phlegmasia cerulea dolens (PCD) is an uncommon condition of acute deep vein thrombosis, characterized by marked swelling of the affected limb with pain and cyanosis. High mortality and morbidity rates have been reported. Early diagnosis, quick and effective treatment are crucial for preventing potential limb loss or even death. Patient concerns: A 39-year-old woman presented to our emergency department with painful swelling and cyanotic discoloration of the left lower limb for 2 days. Diagnoses: Computed tomography revealed thrombosis in the left common iliac vein and inferior vena cava. Angiography demonstrated extensive venous occlusion from the lower inferior vena cava to the left popliteal vein. The diagnosis of PCD was made. Interventions: Systemic anticoagulation with intravenous unfractionated heparin was initiated immediately. Mechanical thrombectomy with Angiojet and angioplasty were performed, and catheter-directed thrombolysis (CDT) was administered subsequently. Outcomes: Follow-up angiography revealed regression of the thrombosis and the opacification of the deep vein was restored. The patient was discharged from the hospital uneventfully. Conclusions: PCD is a rare but potentially limb and life-threatening condition that requires immediate recognition. Treatment should be in a timely manner. Anticoagulation alone may be inadequate and more aggressive management such as CDT and thrombectomy should be considered.